Pengaruh E- Absensi Dan Tambahan Penghasilan Pegawai (Tpp) Terhadap Kinerja Pegawai Di Dinas Tanaman Pangan Dan Hortikultura Provinsi Sumatera Utara - Nia Afdila; Tukimin Lubis; Lukman Nasution; Sari Wulandari (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
The population in this study were employees of the Food Crops and Horticulture Office of North Sumatra Province, totaling 160 employees. The results of using the slovin formula in this study the researchers took a sample of 114 employees of the Food Crops and Horticulture Office of North Sumatra Province. The analysis tool used is SPSS Version 25.00. The results of the t test obtained t-count > t-table (5.127 > 1.6584) and a significant value of 0.000 is less than 0.05 meaning that e-absence has a positive and significant effect on employee performance, so Ha1 is accepted. The value of t-count > t-table (8.399 > 1.6584) and a significant value of 0.000 is less than 0.05 meaning that the Additional Employee Income (TPP) has a positive and significant effect on employee performance, then Ha2 is accepted. Fcount (103.974) > Ftable (3.08), and a significance value of 0.000 <0.05, it can be concluded that the third hypothesis is accepted, meaning that the E-Absence Variable (X1) and Additional Employee Income (X2) have a simultaneous effect on Employee Performance Variable (Y).